2018
DOI: 10.1186/s12904-018-0286-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s and health care provider’s perspectives on music therapy in palliative care – an integrative review

Abstract: BackgroundThe use of music as therapy in multidisciplinary end-of-life care dates back to the 1970s and nowadays music therapy (MT) is one of the most frequently used complementary therapy in in-patient palliative care in the US. However existing research investigated music therapy’s potential impact mainly from one perspective, referring to either a quantitative or qualitative paradigm. The aim of this review is to provide an overview of the users’ and providers’ perspectives on music therapy in palliative ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 33 publications
1
41
0
4
Order By: Relevance
“…Music/art therapy: However, there was moderatequality evidence from three reviews 51,69,94 demonstrating the positive impact of music/art therapy on a The GRADE category is based on identified systematic reviews published between 2013 and February 2018. We used the following reasons for downgrading confidence in the evidence (downgraded by 1 or 2): Study limitation (observational studies start with a low GRADE value), Inconsistency (individual studies do not come to the same conclusions or there is only one study so inconsistency cannot be evaluated), Imprecision (there is no effect estimate, there is no measure of dispersion, or the CI is very broad); we used the systematic review authors' evaluation for other GRADE criteria if there was a formal quality of evidence assessment (see text).…”
Section: (S)mentioning
confidence: 99%
See 2 more Smart Citations
“…Music/art therapy: However, there was moderatequality evidence from three reviews 51,69,94 demonstrating the positive impact of music/art therapy on a The GRADE category is based on identified systematic reviews published between 2013 and February 2018. We used the following reasons for downgrading confidence in the evidence (downgraded by 1 or 2): Study limitation (observational studies start with a low GRADE value), Inconsistency (individual studies do not come to the same conclusions or there is only one study so inconsistency cannot be evaluated), Imprecision (there is no effect estimate, there is no measure of dispersion, or the CI is very broad); we used the systematic review authors' evaluation for other GRADE criteria if there was a formal quality of evidence assessment (see text).…”
Section: (S)mentioning
confidence: 99%
“…Three reviews reported anxiety outcomes for music/art therapies. 51,69,94 One review reported that creative art therapies significantly reduced anxiety (SMD 0.28; CI 0.11e0.44; 25 RCTs) and depression (SMD 0.23; CI 0.05e0.40; 11 RCTs) compared to controls after intervention. 94 Another review found four studies (one RCTand three pre-post) demonstrating positive effects of music therapy on anxiety and three studies (one RCT and two pre-post) demonstrating reduced depression.…”
Section: (Im In)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a medicine that is person-centered, holistic, and not just in disease as it was in the case of the biomedical technique, which fragments the individual according to the pathology, aiming only for healing and not for comfort. 6,7,13 Patients in palliative care often have too much pain that does not stop well with medication, but adjunctive therapies such as music therapy can more effectively alleviate some symptoms, such as fatigue, depression, and relatively common problems in this population. to evoke memories of pleasure and joy associated with the songs that make up the therapeutic arsenal.…”
Section: 1213mentioning
confidence: 99%
“…Опрос, проведенный Британской ассоциацией музыкальных терапевтов среди ее членов в 2017 г., показал, что более половины специалистов ассоциации на постоянной основе задействованы для оказания паллиативной помощи в хосписах [49]. Мета-анализ применения МТ в паллиативной помощи, выполненный в 2018 г. учеными университета в Бергене (Норвегия), и основанный на 67 рандомизированных контролируемых исследованиях (РКИ) с участием в общей сложности более 800 пациентов, продемонстрировал широчайшую область применения метода в паллиативной медицине и выявил непрерывный рост востребованности МТ со стороны пациентов, а также увеличение разнообразия методик, предлагаемых музыкальными терапевтами [50]. Ежегодное увеличение количества исследований МТ в паллиативной медицине, направленных на повышение ее эффективности в облегчении страданий неизлечимых пациентов, дает основания для уверенности в дальнейшем развитии и совершенствовании метода.…”
unclassified